Advances in epidemiological status and pathogenesis of dental fluorosis - Zhang, Kaiqiang; Lu, Zhenfu; Guo, Xiaoying (Frontiers in Cell and Developmental Biology, 2023)
Fluoride is commonly considered a “double-edged sword” because low consumption of fluoride can effectively prevent dental caries, but excessive consumption of fluoride can cause fluorosis. Dental fluorosis (DF) is acharacteristic of fluorosis in the oral cavity that is manifested as tooth color change and evident enamel defect. Presently, the pathogenesis of DF remains unclear. Herein, we have summarized the research progress on the pathogenesis and mechanism of DF in the past 5 years.